Understanding the Marriage Practices of the Sama Bangingi Tribe: Cultural Significance and Social Implications - Ticao, Nurmia Leon; Janang, Sarnila; Taasin, Sitti Aiza; Mohammad, Nhelbourne K. (The Indonesian Institute of Science and Technology Research, 2025)
This study examines the characteristics and cultural practices of marriage among the Sama Bangingi community in Barangay Bolong, Zamboanga City, Philippines. The study emphasizes the significance of promoting modest dowries and straightforward marriage procedures, aiming to make marriage more accessible and financially feasible. By advocating for simplified marriage customs, this research highlights the importance of parents avoiding demanding excessive dowries, which can reduce issues such as elopement and financial strain. The findings reveal that the majority of participants prefer simple, low-cost weddings, mainly due to financial limitations, and that dowries, though minimal, remain a customary aspect of marriage among the Sama Bangingi. This research provides valuable insights for prospective couples, parents, Muslim communities, other cultural groups, and future researchers.